Determinants of Peer Acceptability of Exceptional Children - Heaven, Roberta K.B. (My University, 1988)
Review of available research yields contradictory findings as to the degree of peer acceptance or rejection which exists for learning disabled children. The majority of peer acceptability studies have focused on interpersonal behaviour. These studies emphasize the complexities of peer socialization and the inadequacies of present levels of understanding. An examination of the methodologies of these studies indicates that a number of potential confounds may hinder the identification of factors which may significantly influence peer acceptability. Learning disabled children can be typically identified by some deficit in the areas of academic, social and athletic functions, according to the most common characteristics reported in the literature, however, little research has specifically examined these factors. The primary objectives of this research program were threefold. The first objective was to determine whether or not learning disabled children would be significantly less well accepted by their normal peers in grades 4, 6 and 8 when described on the basis of these three characteristics. The second objective was to systematically examine the relative importance of each of the three characteristics identified collectively in the initial research. The final objective was to assess whether or not an intergroup perspective in contrast to the interpersonal perspective utilized so widely was applicable to the issue of peer acceptance of learning disabled children and whether this approach provided new information to the understanding of these issues. Results indicated that learning disabled characters described on the basis of three characteristics were reliably rated significantly less favourably than normal or handicapped characters on sociometric ratings and intergroup measures. Further systematic evaluation of each factor and combination of factors indicated that while all three were important in determining peer acceptability ratings, academic competence information was the most important, followed closely by social competence information and finally athletic competence information. These findings could be generalized to children in grades 4, 6 and 8. In addition, learning disabled children were found to respond in a similar manner to that of their normal peers. These results are consistent with much of the available literature and provide new information concerning the salience of three key characteristics associated with learning disabled children as a group. Further, Social Identity Theory, the intergroup theory selected for use in these studies, was found to be applicable, consistent with the results obtained and was able to predict outcome in these experiments. Hence, it is concluded that examining peer acceptability of exceptional children from an intergroup perspective contributes to the present understanding of these issues.
Keywords: Psychology; Child Psychology